Factors associated with diet quality of adolescents in Saudi Arabia - Mumena, Walaa Abdullah (Frontiers in Public Health, 2024)
Introduction: Research exploring factors that may influence the diet quality of adolescents in the Middle East are very limited. We aimed to investigate factors associated with diet quality and the weight status of adolescents in Saudi Arabia. Methods: A cross-sectional study that included 638 healthy adolescents aged between 11-18 years who were randomly recruited from 16 private and public middle- and high-schools located in two Saudi cities (Jeddah and Madinah). All participants were given an envelope for parents to collect socioeconomic data. Diet quality and anthropometric data of adolescents were evaluated at school. Results: Median diet quality score was higher among males compared to female adolescents (10.00 (8.00-11.00) vs. 9.00 (8.00-10.0), respectively, p= 0.018). Median diet quality score was significantly higher among adolescents residing in Jeddah compared to adolescents residing in Madinah (10.00 (9.00-11.0) vs. 9.00 (8.00-10.0), respectively, p= 0.002). Stepwise linear regression analysis indicated that city of residence (B= -0.53, SE= 0.16 [95% CI: -0.83 to -0.22]), and child’s sex (B= -0.34, SE= 0.15 [95% CI: -0.64 to -0.05]) were associated with diet quality scores of adolescents in Saudi Arabia. Discussion: Future longitudinal research should be directed to further investigate other possible factors influencing the diet quality of adolescents and individuals from other age groups in Saudi Arabia.